Microtensile Bond Strength, Marginal Leakage, and Antibacterial Effect of Bulk Fill Resin Composite with Alkaline Fillers versus Incremental Nanohybrid Composite Resin - Mohamed, Nada Ismail; Safy, Rehab Khalil; Elezz, Ahmed Fawzy Abo (European Journal of Dentistry, 2020)
Objective This study aimed to investigate the microtensile bond strength (µTBS), microleakage, and antibacterial effect of bulk fill resin composite with alkaline fillers (alkasite) (alkaline fillers such as barium aluminum silicate glass and ytterbium trifluoride) in comparison to incremental nanohybrid resin composite.Materials and Methods µTBS was evaluated by using 30 human mandibular molars. Teeth were randomly divided into three groups (C): nanohybrid resin composite (C0), self-cured alkasite (C1), and dual-cured alkasite (C2). Each group was subdivided into two subgroups according to the bulk thickness: 4 mm (T1) and 6 mm (T2). The occlusal enamel of teeth was removed and the resin composite was applied to a flat dentin surface. Then, teeth were sectioned into beams to be tested under tension. For microleakage testing, mesio-occlusal class II cavities were prepared in 15 molars and divided into three groups as mentioned before. Following this, cavities were restored, thermocycled, immersed in a dye, sectioned mesiodistally, and then dye penetration was assessed. The antibacterial effect of both tested materials was evaluated using agar disc diffusion and broth dilution methods against chlorhexidine as a control positive group.Results There was no significant difference in µTBS between all tested groups. Bulk fill self-cured alkasite showed the lowest microleakage value followed by bulk fill dual-cured alkasite and incremental nanohybrid resin composite, respectively. Also, cervical microleakage showed significantly higher mean value than the occlusal one. The antibacterial effect of alkasite was less than chlorhexidine. Alkasite showed maximum broth clarity at lowest tested bacterial concentration.Conclusion Resin composite with alkaline fillers was characterized by good µTBS and marginal integrity with weak antibacterial effect.
Keywords: alkasite; microtensile bond strength; microleakage; antibacterial effect